Targets, threats and (dis)trust: The managerial troika for public school principals in Chile - Carmen Montecinos; Luis Ahumada; Sergio Galdames; Fabián Campos; María Verónica Leiva (Arizona State University, 2015)
Public education in Chile has been steadily losing students as a result of the implementation, for the last 35 years, of a market model. In this paper we exemplify how a structural problem (public schools' declining enrollment) created by neoliberal educational policies is transformed into an individual problem to be managed by the public school principal. Principals must sign a performance-based contract that specifies sanctions and incentives for meeting enrollment targets. The current paper examines, through data produced by in-depth interviews and shadowing, how 19 principals worked toward that target. Findings show that to manage enrollment principals spent, on average, 24% of their time performing marketing tasks. Principals, thus, have developed an entrepreneurial self, which is promoted by quasi-market school governance models. Through this entrepreneurship they manage various threats that represent barriers to the possibilities for meeting enrollment targets.